PENINGKATAN PEMAHAMAN SPASIAL DAN HASIL BELAJAR MELALUI MEDIA AUGMENTED REALITY (AR) TERINTEGRASI GROWTH MINDSET PADA SISTEM PENCERNAAN MANUSIA - Purwo Haryono; Anisa Diah Wardani; Annisa Nur Aeni; Atika Kusumastuti; Atthahirah Azzahra; Aulli Qzara Ainun Nisa Mufi Dayanti; Aulyalifa Noorafasita; Septiana Wijayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the use of Augmented Reality (AR) media integrated with growth mindset in improving spatial understanding and student learning outcomes in the human digestive system material in grade V of SDN 1 Jonggrangan. The study used the Classroom Action Research (CAR) method which was carried out by students in two cycles with the stages of planning, action implementation, observation, and reflection. The subjects of this action research were grade V students of SD N 1 Jonggrangan in the 2025/2026 academic year. There were 8 students in grade V, consisting of 5 male students and 3 female students. While the object of this study was the overall learning improvement activities, especially the learning outcomes and spatial abilities of students during the learning process of the human digestive system material. Data collection techniques included observation, evaluation tests, and questionnaires. Quantitative data were analyzed using descriptive statistics in the form of averages and percentages of learning completion, while qualitative data were analyzed descriptively based on the results of observations and growth mindset questionnaires. The results of this study indicate that the use of Augmented Reality media in science learning is able to create an interactive and enjoyable learning experience so that it can improve spatial abilities while improving student learning outcomes. In the learning enthusiasm indicator, the percentage of positive student responses increased from 79.16% in the pre-cycle to 91.67% in the first cycle and reached 100% in the second cycle. The same increase also occurred in the material understanding indicator, which was 79.71% in the pre-cycle and became 95.84% in the first cycle and reached 100% in the first cycle. In addition, the ability confidence indicator increased from 79.17% in the pre-cycle to 95.83% in the first cycle and reached 100% in the second cycle. This is supported by the results of the N-Gain test which showed an increase in students' spatial understanding across all indicators gradually starting from the pre-cycle, cycle I, to cycle II. The N-Gain value increased from 0.7317 to 1.00 indicating that the use of AR media integrated with growth mindset intervention can improve students' spatial abilities. In addition, the evaluation results showed that 7 out of 8 students (87.5%) achieved learning mastery with a class average score of 86.88. The improvement in the evaluation results shows that the use of AR media can help students understand the material on the human digestive system more easily through interactive and concrete visualizations.